Novel Techniques with the Aid of a Staged CBCT Guided Surgical Protocol - Evdokia Chasioti; Mohammed Sayed; Howard Drew (Case Reports in Dentistry)
The case report will present some novel techniques for using a “staged” protocol utilizing strategic periodontally involved teeth as transitional abutments in combination with CBCT guided implant surgery. Staging the case prevented premature loading of the grafted sites during the healing phase. A CBCT following a tenting screw guided bone regeneration procedure ensured adequate bone to place an implant fixture. Proper assessment of the CBCT allowed the surgeon to do an osteotome internal sinus lift in an optimum location. The depth of the bone needed for the osteotome sinus floor elevation was planned. The staged appliance allowed these sinus-augmented sites to heal for an extended period of time compared to implants, which were uncovered and loaded at an earlier time frame. The staged protocol and CBCT analysis enabled the immediate implants to be placed in proper alignment to the adjacent fixture. After teeth were extracted, the osseointegrated implants were converted to abutments for the transitional appliance. Finally, the staged protocol allowed for soft tissue enhancement in the implant and pontic areas prior to final insertion of the prosthesis.